2021
DOI: 10.3390/agronomy11071411
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Determination of the Effects of He–Ne Laser Irradiation on Seed Thermodynamics, Germination Attributes and Metabolites of Safflower (Carthamus tinctorius L.) in Relation with the Activities of Germination Enzymes

Abstract: The present investigation was undertaken to assess the effects of different doses (100, 300, and 500 mJ) of low power He–Ne laser (632.8 nm) irradiation on seed germination and thermodynamics attributes and activities of potential germinating enzymes in relation with changes in seed metabolites. He–Ne laser seed irradiation increased the amylase (Amy), protease (Pro) and glucosidase (Gluco) activities, with a significant improvement in seed thermodynamics and seed germination attributes. A fast increase was fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 50 publications
(89 reference statements)
4
10
0
Order By: Relevance
“…Likewise, the processes are necessary for healthy growth in the salt stressed condition like essential physiological and biochemical disrupting and severe damage of cellular by excessive generation of reactive oxygen species ( Saleem et al., 2020 ; Ghafar et al., 2021 ; Hameed et al., 2021 ; Perveen et al., 2021 ). The largest cellular generation of ROS, particularly H 2 O 2 , promoted lipid peroxidation of cellular membranes ( Kazemi et al., 2019 ; Saleem et al., 2020 ), resulting in the synthesis of higher MDA in plant tissues in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, the processes are necessary for healthy growth in the salt stressed condition like essential physiological and biochemical disrupting and severe damage of cellular by excessive generation of reactive oxygen species ( Saleem et al., 2020 ; Ghafar et al., 2021 ; Hameed et al., 2021 ; Perveen et al., 2021 ). The largest cellular generation of ROS, particularly H 2 O 2 , promoted lipid peroxidation of cellular membranes ( Kazemi et al., 2019 ; Saleem et al., 2020 ), resulting in the synthesis of higher MDA in plant tissues in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that reducing, non-reducing and total sugar contents of grape berries were increased with increasing concentration of micronutrients (Table 4). Such an increase in sugar contents of grape berries could be related to the increased chlorophyll contents and the higher photosynthesis rate achieved through supplemental sprays of Fe, B and Zn [51]; similar findings were reported in apple and grapevines [52][53][54]. Higher sugar contents as a result of foliar sprays of micronutrients have also been reported in strawberry, pomegranate, and grapes [55][56][57].…”
Section: Discussionsupporting
confidence: 64%
“…In this experiment, irradiating the seeds once the germination metabolism had started, due to the prior seed soaking, improved the effectiveness of the laser irradiation in relation to that obtained in Experiment 3, resulting in significant differences (p ≤ 0.05). This was in accordance with that reported by Perveen et al [37,59] for sunflower and safflower, respectively, who obtained good germination results irradiating seeds that had been previously soaked in water with a He-Ne laser.…”
Section: Methodssupporting
confidence: 93%
“…On the other hand, other studies on many species found that irradiation with laser light improved germination parameters, including wheat (Triticum aestivum L. [36]), lupine (Lupinus albus L.) and bean (Vicia faba L.) [38], radish (Raphanus sativus L. [57]), soybean (Glycine max L. [58]), safflower (Carthamus tinctorius L. [59]), sunflower (Helianthus annuus L. [37]) and Chinese woad (Isatis indigotica L. [34]). The laser light can affect the thermodynamic ≤ parameters of the seeds by increasing their internal energy, affecting the enzymatic activity (mainly of amylases, proteases and glucosidases), which may positively influence the germination [36].…”
mentioning
confidence: 99%